От редактора - Bukh, Vladimir (проект байкал, 2006)
How should we build on the coast of Lake Baikal? Better never to build than to build like we do it at present. Or it would be better if a human being does not interfere in the lake area at all? This thought occurs more often as it becomes evident that people’s presence on the coast does not do any good to Lake Baikal. It was reckless of the tsar to encircle the lake with the railway on the southern side. It was cynical of the «central planning» regime to press it from the north with the second iron hand. Now the oil pipeline is coming closer to Lake Baikal while guaranteeing technical perfection. Why not? This action keeps to the logic of previous ones. Consumer civilization is skillfully seizing the lake: settlements, industry, communications, and today’s passion for country houses, and tourism… Remaining unique both naturally and mythologically, Lake Baikal is under growing anthropological pressure. To prevent it from losing its inherent uniqueness we probably cannot do without architects as «synthetical» specialists.